liltj0
Answered

At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Solve 42 = 3(-4a) + 6

Sagot :

Answer: a = -3

Step-by-step explanation:

42 = 3(-4a) + 6

42 = -12a + 6

Subtract 6 from both sides

36 = -12a

Divide both sides by -12

-3 = a

a = -3